Verification of Steel Plate as Target for 9-Meter-High Cask Drop Tests - Heloisa Maria Santos Oliveira; Lucca Daré Venturini; Cláudio Cunha Lopes; Luiz Leite da Silva; Vitor Vasconcelos Araújo Silva; Emerson Giovani Rabello; Graiciany de Paula Barros; Andre Augusto Campagnole dos Santos (Brazilian Journal of Radiation Sciences)
The nuclear fuel cycle encompasses processes from uranium mining to the final disposal or packaging of radioactive waste. For the final packaging, radioactive waste must be transported in specially designed casks. The certification of these casks involves a series of prescribed tests, as outlined by standards and regulations such as CNEN NN 5.05 [1], NUREG-2125 [2], and IAEA SSG-26 [3]. These tests simulate hypothetical accidental transportation conditions, including free drop tests from a height of 9 meters, penetration tests, fire exposure tests, and immersion tests. To satisfy the drop and penetration tests, the cask must be dropped onto a target with a flat, horizontal, and as much as technically feasible, unyielding surface. The standards specify that “the target for drop tests is an essentially unyielding surface,” meaning it is “hard and heavy enough that the package absorbs nearly all of the impact energy, with the target absorbing very little energy.” This unyielding surface is intended to inflict damage on the package equivalent to or greater than what might occur during actual transportation impacts. The use of such a target ensures that analyses and tests can be compared and, if necessary, accurately repeated. This study evaluates the 9-meter drop of a package with a mass equivalent to a 1:4 scale type B(U) transportation cask onto a steel plate fixed to a concrete slab, aiming to qualify the target represented by the steel plate. The numerical simulation was conducted using LS-Prepost® V4.8.29 [4].